2020
DOI: 10.1109/access.2020.3035076
|View full text |Cite
|
Sign up to set email alerts
|

Three-Factor UCSSO Scheme With Fast Authentication and Privacy Protection for Telecare Medicine Information Systems

Abstract: Electronic healthcare (e-health) has gained more and more research attention in recent years, due to its flexibility and convenience. E-health is efficiently enabled by telecare medicine information system (TMIS). TMIS provides seamless transfer and timely sharing of medical information for specific healthcare services. Since communications in TMIS are carried out through unreliable channels, data security and user privacy concerns become prominent. With traditional single-server architecture, users must store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…• Our work introduces a single sign-on (SSO) solution [39,40,42] for group services in a multi-server environment. This solution allows users to use a single set of credentials stored in their smart cards to obtain services provided by multiple servers.…”
Section: A Rabin Cryptosystemmentioning
confidence: 99%
See 3 more Smart Citations
“…• Our work introduces a single sign-on (SSO) solution [39,40,42] for group services in a multi-server environment. This solution allows users to use a single set of credentials stored in their smart cards to obtain services provided by multiple servers.…”
Section: A Rabin Cryptosystemmentioning
confidence: 99%
“…Jiang et al [41] presented a three-factor authentication scheme with privacy protection for e-health clouds. It is observed that Jiang et al [41]'s scheme is not resilient to replay attacks, stolen smart card attacks and desynchronization attacks [39]. Moreover, Liu et at.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…of attributes; --: not available. Based on [ 1 , 63 ]: ≈ 0.72036 , ≈ 0.2622 , ≈ 0.00069 , ≈ 0.72036 , and ≈ 0.72036 .…”
Section: Figurementioning
confidence: 99%